Endometriosis and Mortality Risk in US Women: Findings From NHANES 1999–2006 - Liu L; Shao C; Li L; Wu N (International Journal of Women's Health, 2025)
Lijie Liu,1,* Chuan Shao,2,* Lujia Li,1 Nan Wu2 1Department of Health Care, People’s Liberation Army Navy 971 Hospital, Qingdao, 266071, People’s Republic of China; 2Department of Neurosurgery, Chongqing General Hospital, Chongqing University, Chongqing, 401147, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lujia Li, Department of Health Care, People’s Liberation Army Navy 971 Hospital, Shandong Road, Qingdao, 266071, People’s Republic of China, Email li_lujia2025@yeah.net Nan Wu, Department of Neurosurgery, Chongqing General Hospital, Chongqing University, 118 Xingguang Boulevard, Liang Jiang New Area, Chongqing, 401147, People’s Republic of China, Tel/Fax +86-23-63390700, Email wunan@cqu.edu.cnObjective: Less is known about the link between mortality and endometriosis, an often chronic, inflammatory gynecologic condition. We assessed the association between endometriosis and all-cause and cause-specific mortality using a retrospective cohort study design based on data from the National Health and Nutrition Examination Survey (NHANES) 1999– 2006.Materials and Methods: Both crude and multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for endometriosis and age at endometriosis with all-cause mortality were estimated using weighted Cox proportional hazards regression. Moreover, we also performed an exploratory analysis assessing the relationship between endometriosis and mortality from cancer and cardiovascular disease (CVD).Results: Between 1999 and 2006, a cohort of 5552 women aged 20 to 54 years was studied, representing a weighted population of approximately 66.07 million. Over a median follow-up duration of 16.75 years, 290 participants died from various causes, which extrapolates to an estimated 3,411,632 female deaths in the broader population. A non-significant association was identified between endometriosis and all-cause mortality (HR 1.51, 95% CI: 0.97– 2.34, P = 0.066), cancer (HR 1.45, 95% CI: 0.76– 2.78, P = 0.260), or CVD (HR 1.75, 95% CI: 0.65– 4.73, P = 0.271) mortality. When accounting for the age at endometriosis was diagnosed, the association was significant only among women diagnosed at age ≤ 30 years (HR = 1.87, 95% CI: 1.15– 3.03, P = 0.011 for all-cause mortality; HR = 4.37, 95% CI: 1.54– 12.36, P = 0.005 for CVD mortality) and was not significant for those diagnosed after age 30 years.Conclusion: In conclusion, women diagnosed with endometriosis at a younger age may be associated with an increased risk of mortality.Keywords: endometriosis, mortality, cohort, NHANES, risk